Emigration and wages: the EU enlargement experiment - Elsner, Benjamin (Dublin, 2011)
"This paper studies the impact of a large emigration wave on real wages in the source country. Following EU enlargement in 2004, a large share of the workforce of the Central and Eastern Europe emigrated to Western Europe. Using data from Lithuania for the calibration of a factor demand model I show that emigration had a significant short-run impact on real wages in the source country. In particular, emigration led to a change in the wage distribution between young and old workers. The wages of young workers increased by 6%, whereas the wages of old workers decreased by around 1%. On the contrary, I find no effect on the wage distribution between workers of different education levels."